Simulation and Experimental Study of Light and Thermal Environment of Photovoltaic Greenhouse in Tropical Area Based on Design Builder - Jian Liu (MDPI AG, 2021)
In order to study the adaptability of photovoltaic greenhouses to climate in tropical areas, a photovoltaic greenhouse model (photovoltaic panel coverage rate: 76.9%) was built in this study according to a 1:1 proportion. The distribution law of the indoor illuminance, temperature, and humidity were studied simultaneously in the photovoltaic greenhouse by actual measurements and simulation. The filed data are shown as follows: (1) Illuminance: in limited rain winter, the average illuminance and light transmittance were 7.02 kLux and 25.77%, respectively (10:00–16:00); but in different weather conditions during summer, the average illuminance and light transmittance were 15.47 kLux and 32.35%, respectively (9:00–16:00). (2) Temperature and humidity: the indoor temperatures of the greenhouse were between 22.1 and 29.3 °C in limited rain winter, with a relative small temperature difference between indoor and outdoor environments; the relative humidity values were between 69% and 97%; but in summer, the temperatures at all indoor test site were higher than outdoor sites, with an average temperature difference of 2.7 °C and relative humidity values between 46% and 94%. According to the simulation by Design Builder, the average light transmittances were 33.09% in winter and 37.54% in summer, the temperature difference between winter and summer was less than 1 °C, and the relative humidity decreased with the increase of temperature, which basically coincided with the filed data. The results of the analysis showed that the illuminance, temperature and humidity of the photovoltaic greenhouse can satisfy the production requirements of shade-enduring and neutral crops. At the same time, by comparing the illumination, temperature and humidity of the photovoltaic greenhouse with that of an ordinary greenhouse, the former had good adaptability to climate in tropical areas, which can achieve the goal of photovoltaic generation and agricultural production synchronously.